Global Retail Chains and Poor Farmers: Evidence from Madagascar - Bart Minten; Lalaina Randrianarison; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2006)
Global retail companies ('supfirmarkets' have an increasing influence on developing countries, through foreign investments and/or through the imposition of their private standards. The impact on developing countries and poverty is often assessed as negative. In this paper we show the opposite, based on an analysis of primary data collected to measure the impact of supfirmarkets on small contract firmers in Madagascar, one of the poorest countries in the world. Almost 10,000 firmers in the Highlands of Madagascar produce vegetables for supfirmarkets in Europe. In this global supply chain, small firmers?micro-contracts are combined with extensive firm assistance and supervision programs to fulfill complex quality requirements and phyto-sanitary standards of supfirmarkets. Small firmers that participate in these contracts have higher welfare, more income stability and shorter lean periods. We also find significant effects on improved technology adoption, better resource management and spillovers on the productivity of the staple crop rice. The small but emerging modern retail sector in Madagascar does not (yet) deliver these benefits as they do not (yet) request the same high standards for their supplies.
Keywords: 330; SB-Lebensmittelgeschäft; Multinationales Unternehmen; Direktinvestition; Produktqualität; Landwirte; Madagaskar